2004
DOI: 10.1007/s00018-004-4341-3
|View full text |Cite
|
Sign up to set email alerts
|

Terrein: a new melanogenesis inhibitor and its mechanism

Abstract: Terrein is a bioactive fungal metabolite whose effects are almost unknown. In this study, we found for the first time that terrein has a strong hypopigmentary effect in a spontaneously immortalized mouse melanocyte cell line, Mel-Ab. Treatment of Mel-Ab cells with terrein (10-100 microM) for 4 days significantly reduced melanin levels in a dose-dependent manner. In addition, terrein at the same concentration also reduced tyrosinase activity. We then investigated whether terrein influences the extracellular sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 90 publications
4
106
0
1
Order By: Relevance
“…However, the biological effects of 2 have been almost unknown. Recently, 2 was reported to inhibit the melanogenesis [20] and the epidermal proliferation of skin equivalents [21]. Although whether 2 affects the angiogenesis-related factors has been unknown before, we have shown here that 1 and 2 inhibited angiogenin secretion from LNCaP-CR cells with IC 50 values of 13 mM, respectively (Table 3).…”
Section: Effect Of 1 and 2 On Angiogenin Secretion From Prostatesupporting
confidence: 50%
“…However, the biological effects of 2 have been almost unknown. Recently, 2 was reported to inhibit the melanogenesis [20] and the epidermal proliferation of skin equivalents [21]. Although whether 2 affects the angiogenesis-related factors has been unknown before, we have shown here that 1 and 2 inhibited angiogenin secretion from LNCaP-CR cells with IC 50 values of 13 mM, respectively (Table 3).…”
Section: Effect Of 1 and 2 On Angiogenin Secretion From Prostatesupporting
confidence: 50%
“…Park et al (18) indicated that the activated ERK pathway may inhibit melanin synthesis through decreasing the expression of the microphthalmia-associated transcription factor gene, and an alternative study suggested the p38 MAPK pathway may promote melanin synthesis through increasing the expression of the tyrosinase gene (19). Furthermore the JNK pathway may be implicated in the inhibition of melanin synthesis (20).…”
Section: Discussionmentioning
confidence: 99%
“…The melanin inhibition effect of compound [1] was not due to cytotoxicity, because the melanin assay was performed by adjusting the number of cells and the inhibition of cell growth was observed at the concentration of 0.25 mg/ml (0.53 mM). Several other melanin biosynthesis inhibitors that do not inhibit tyrosinase activity have been isolated from plants; these include 4,5-dihydroxy-3-propenyl-2-cyclopenten-1-one (terrein; IC 50 Լ30 mM) from Penicillium species, 21) piperlonguminine (IC 50 Լ10 mM) from Piper longum (Piperaceae), 12) and coumarin compounds such as soimperatorin and imperatorin (IC 50 Ͼ100 mM) from Angelica dahurica. 22) Thus, compound [1] is one of the most potent melanin Total RNA was extracted from cells were cultured for 1 d in medium containing 0.125 mg/ml of 3b,16b-dihydroxy-21a-hydroperoxy-20(30)-taraxastene [1].…”
Section: Discussionmentioning
confidence: 99%